Mongolia : The Politics of Public Investment - Hasnain, Zahid (World Bank, Washington, DC, 2014)
Why do politicians distort public investments? And given that public investments are poor, because presumably that is what is politically rational, what types of reforms are likely to be both Efficiency improving and compatible with the interests of politicians? This chapter explores these two questions in the context of Mongolia. It argues that Mongolian members of parliament MPs have an incentive to over spend on smaller projects that bring benefits to specific geographical localities and to under spend on large infrastructure that will bring economic benefits to Mongolia on the whole. The incentive for the former is that MPs internalize the political benefits from the provision of particular, targeted benefits to specific communities. This chapter is inductive in its structure. First, the broader public expenditure patterns in Mongolia are analyzed in order to identify policy maker s priorities that are, revealed preferences. Then the public investment management system is examined in depth, identifying the main Technical and structural weaknesses in the system. Following that is an analysis of the interests of Key political actors that are served by poor investments. Given these political incentives, the final section proposes some incentive compatible reform options.